Pengaruh penambahan abu sekam padi dan serat kelapa pada kuat tekan bata tanah putih - Kristiana Bebhe; Richardus Daton (ARTEKS : Jurnal Teknik Arsitektur, 2021)
White soil is a common material in Timor Island, especially in Kupang, usually molded into bricks without adding sand due to its high sand content which has been recorded to be between 30-65%. This study was, therefore, conducted to determine the effect of adding husk ash and coconut fiber on the compressive strength of white soil bricks mixture using an experimental method. The process involved drying the white soil bricks using winding for 28 days after molding after which the compressive strengths for the coconut fiber with cement and rice husk with cement were measured. The results showed a ratio of 1 coconut fiber to 1 cement produced 7 white soil with compressive strength at 147 kg/cm² while 1.5 rice husk ash to 1 cement produced 7 white soil with 114.3 kg/cm². These were, however, observed to be much higher than the findings of previous studies which used 1 cement to 7 white soil to produce 51.9 kg/cm². This, therefore, means the compressive strength produced in this study exceeds the value for quality 1 bricks based on SNI 03-0349-1989 for loaded and unprotected constructions.